Protective effects of novel organic selenium compounds against oxidative stress in the nematode Caenorhabditis elegans. (2015) - Stefanello, Sílvio Terra; Gubert, Priscila; Puntel, Bruna; Mizdal, Caren Rigon; Campos, Marli Matiko Anraku de; Salman, Syed M.; Dornelles, Luciano; Avila, Daiana Silva; Aschner, Michael; Soares, Félix Alexandre Antunes
Highlights: Novel organic selenium compounds presented low toxicity over C. elegans survival. Defecation cycles were decreased by Novel organic selenium compounds, except C1. Novel organic selenium compounds, except C1 decreased AChE enzyme activity. All compounds tested prevented from juglone stress. C2 selenium compound decreased GST-4::GFP fluorescence under juglone stress. Abstract: Organic selenium compounds possess numerous biological properties, including antioxidant activity. Yet, the high toxicity of some of them, such as diphenyl diselenide (DPDS), is a limiting factor in their current usage. Accordingly, we tested four novel organic selenium compounds in the non-parasite nematode Caenorhabditis elegans and compared their efficacy to DPDS. The novel organic selenium compounds are β-selenoamines 1-phenyl-3-( p -tolylselanyl)propan-2-amine (C1) and 1-(2-methoxyphenylselanyl)-3-phenylpropan-2-amine (C2) and analogs of DPDS 1, 2-bis(2-methoxyphenyl)diselenide (C3) and 1, 2-bis p -tolyldiselenide (C4). Synchronized worms at the L4 larval stage were exposed for one hour in M9 buffer to these compounds. Oxidative stress conditions were induced by juglone (200 μM) and heat shock (35 °C). Moreover, we evaluated C. elegans behavior, GST-4::GFP (glutathione S-transferase) expression and the activity of acetylcholinesterase (AChE). All tested compounds efficiently restored viability in juglone stressed worms. However, DPDS, C2, C3 and C4 significantly decreased the defecation cycle time. Juglone-induced GST-4::GFP expression was not attenuated in worms pretreated with the novel compounds, except with C2. Finally, AChE activity was reduced by DPDS, C2, C3 and C4. To our knowledge, this is study firstly showed the effects of C1, C2, C3 and C4 selenium-derived compounds in C. elegans . Low toxic effects were noted, except for reduction in the defecation cycle, which is likely associated with AChE inhibition. The juglone-induced stress (reduced viability) was fully reversed by compounds to control animal levels. C2 was also efficient in reducing the juglone-induced GST-4::GFP expression, suggesting the latter may mediate the stress induced by this compound. Future studies could be profitably directed at addressing additional molecular mechanisms that mediate the protective effects of these novel organic selenium compounds.